Efeito da espessura da cerâmica de infraestrutura e cobertura de um sistema a base de dissilicato de lítio na sua cor e opacidade - Bueno, Rodrigo Salbego (2013)
The aim of this study was to determine the influence of substruture and veneer ceramic thickness variation, of a lithium disilicate all ceramic system, in its color and opacity. The sample was composed by of 12 specimens, disc shaped, with 12mm in diameter and 4mm in thickness (2mm of substruture ceramic and 2mm of veneer ceramic). Sequential wear of 0,5mm were performed in each specimen, initially in the substruture ceramic and subsequenty in the veneer ceramic, upto 1.0mm of total final thickness (0,5mm of substruture and 0,5mm of veneer ceramic). The L*, a* and b* parameters of the CIELab system and the opacity percentage (Op) were measured using an spectrophotometer at base line and after each wear. The opacity percentage variation (ΔOp) and color variation (ΔE) among groups were obtained. Data were tabulated and analysed at 5% significance level. All the evaluated color parameters showed significant difference among groups. OP decreased with ceramic decreasing thickness, with greater changes in the venner ceramic groups. ΔE was higher when comparing groups with lower ceramic thickness. Furthermore, ΔOP was directly proportional to ΔE. It could be concluded that color and opacity are influenced by the thickness variation of the all ceramic system tested. The opacity percentage was more dependent of the veneer ceramic than the substruture ceramic. The opacity variation is correlated to color variation.